I have homework, which I've seen solution with which I have some problem.

The homework is to find time evolution of state $|\psi(t)\rangle$, if the hamiltonian of the state is $\hat{\textbf{H}}=\epsilon \hat{\textbf{P}} $, where $\hat{\textbf{P}}$ is projection operator and $\epsilon$ some energy dim constant.

So, we can begin with equation $$ |\psi(t)\rangle = \hat{\textbf{U}}|\psi(0)\rangle,$$ where $\hat{\textbf{U}}=\mathrm{e}^{-it\hat{\textbf{H}}}$.

Then we can write $$ \hat{\textbf{U}}|\psi(0)\rangle = \mathrm{e}^{-it\hat{\textbf{H}}} |\psi(0)\rangle = \mathrm{e}^{-it\epsilon\hat{\textbf{P}}} |\psi(0)\rangle = \left(\sum_{n=0}^\infty \frac{1}{n!}(it\epsilon\hat{\textbf{P}})^n\right)|\psi(0)\rangle = \left[ \hat{1} + \sum_{n=1}^\infty \frac{1}{n!}(it\epsilon)^n \hat{\textbf{P}} \right] |\psi(0)\rangle = \left[\hat{1}+ \left(\sum_{n=1}^\infty \frac{1}{n!}(it\epsilon)^n + \hat{1} - \hat{1} \right) \hat{\textbf{P}}\right]|\psi(0)\rangle = \left[\hat{1}+ \left(\sum_{n=0}^\infty \frac{1}{n!}(it\epsilon)^n - \hat{1} \right) \hat{\textbf{P}}\right]|\psi(0)\rangle = \left[\hat{1}- \hat{\textbf{P}} + \sum_{n=0}^\infty \frac{1}{n!}(it\epsilon)^n \hat{\textbf{P}}\right]|\psi(0)\rangle = \left[\hat{\textbf{Q}} + \sum_{n=0}^\infty \frac{1}{n!}(it\epsilon)^n \hat{\textbf{P}}\right]|\psi(0)\rangle = \left[\hat{\textbf{Q}} + \hat{\textbf{P}} \mathrm{e}^{i\epsilon t} \right]|\psi(0)\rangle. $$

And ok, I understand i mathematically, but I don't get why we can't end this lot earlier like here $$ \hat{\textbf{U}}|\psi(0)\rangle = \mathrm{e}^{-it\hat{\textbf{H}}} |\psi(0)\rangle = \mathrm{e}^{-it\epsilon\hat{\textbf{P}}} |\psi(0)\rangle = \left(\sum_{n=0}^\infty \frac{1}{n!}(it\epsilon\hat{\textbf{P}})^n\right)|\psi(0)\rangle = \left(\sum_{n=0}^\infty \frac{1}{n!}(it\epsilon)^n\hat{\textbf{P}}\right)|\psi(0)\rangle = \hat{\textbf{P}}\mathrm{e}^{i\epsilon t} |\psi(0)\rangle. $$

Is this something with index? I have to first rewrite sum to get rid of $\hat{\textbf{P}} = \hat{1}$ and then pull out $\hat{\textbf{P}}$ from sum and then minus unitary operator?


1 Answer 1


Note that $\hat{\mathbf{P}}^n = \hat{\mathbf{P}}$ only holds if $n\neq 0$, so your manipulation is incorrect. You need to extract the $n=0$ case before you replace $\hat{\mathbf P}^n$ with $\hat{\mathbf P}$, which is why the additional steps in the correct solution are required.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.